LANGGA BUWA DANCE AS A SYMBOL OF GENDER EQUALITY MOVEMENT FOR CULVERT WOMEN - Nurlia lia Djafar (JURNAL PAKARENA, 2021)
The research aims to analyze the symbols and meanings contained in Muraji Bereki's Langga Buwa dance. Langga Buwa is a dance that depicts the women's martial arts activities of Gorontalo originating from Langga (self-defense without weapons) and Longgo (self-defense using weapons) which are only performed by Gorontalo men. This research is useful for interpreting the symbols and meanings present by researchers and choreographers who both have the same cultural background as the people of Gorontalo. The method used in this research is to examine each symbol in dance that is influenced by the social system with the various cultures surrounding it which is carried out qualitatively. The result of the research is that everything that is presented through movement, dancers is related to concepts, general ideas, patterns, and forms, giving rise to symbols involving denotative and connotative meanings. This research as a whole contributes to seeing the analysis of the form of Langga Buwa dance performances reflecting gender equality which wants to show the existence of women in fulfilling their rights to be equal to men. Gender differences are only in gender, while the attitudes and characteristics of each are something that can be exchanged so that men and women should receive equal treatment for both their rights and obligations in social life